Overcoming Complex Employment Barriers for Older Individuals: Measures and Opportunities for Enhancement - Moskvina, Julija (Socialinė teorija, empirija, politika ir praktika, 2023)
In the context of the rapidly ageing Lithuanian society, it is important to create the conditions for the effective use of the potential of older people, including the sphere of employment. Although the employment rate of older Lithuanians is higher than the EU average, older people remain a vulnerable group of workers, especially in the face of labour market crises. The withdrawal from the labor market is attributable to inadequacies in qualifications or education that fail to align with the exigencies of the labor market, compromised health, adverse working conditions, and assorted factors concomitantly diminishing employment prospects. Reintegration into the labor market poses a formidable challenge for older individuals who have previously disengaged from it. The complex causes of older people’s exit from the labour market imply a comprehensive solution, but so far the country’s policies for older people have not sufficiently developed an integrated approach to enhancing employability, and the application of pesonalised measures is the responsibility of particular institutions. The aim of the article is to assess the capacities of the current institutional infrastructure of public employment policies to respond to complex obstacles to the employment of elderly individuals and to identify relevant directions for the development of institutional collaboration in this sphere. Based on the latest statistical and analytical information, the paper identifies the current trends in employment and unemployment of the country’s elderly population and identifies the main factors determining their vulnerability in the labour market. It analyses the employment measures implemented by the Public Employment Service for currently unemployed older people. Based on the analysis, proposals are presented for the improvement of the measures in place, with particular emphasis on the development of institutional cooperation in the provision of comprehensive integration services.